The Growth Determinant in the Industrial Sector Featured in East Java Province - Rasyid, Mohtar (JEJAK: Jurnal Ekonomi dan Kebijakan, 2015)
This article aims toanalyzethe main determining factorof growthof industrialsector, especiallythe small scale industriesin East Javaover the past decade. Using theofthe Cobb-Douglas production functionapproach, this research assessedinputfactorconsisting oflabor, capitalandrawmaterials.This study used apooling regression modelto estimate the coefficient of production function fromfourgroups ofselected industries namely:the food industry, textile industry, wood industryandpaperindustry. The results showedthat the sourceof growthfor the industryisstilldominatedbythe physicalgrowth ofinputandnot byproductivity growth. As a result, in the long rungrowth ofthe industry is difficulttobesustainable and relativelyvulnerable toeconomic shocks. Based onthese findingssuggested thatpolicy makersfocus more onefforts toimprove the quality ofinputs, in particularinputqualityhuman resourcesor labor.Â Â